OP0190 Smoking is Not Primarily Associated with ACPA, but with the Presence of Multiple Autoantibodies in RA. (23rd January 2014) - Muhammad, A.; van Wesemael, T.; Kochi, Y.; Mjaavatten, M.; Wevers-de Boer, K.; Allaart, C.; Trouw, L.; Suzuki, A.; Yamamoto, K.; Huizinga, T.; Toes, R.; van der Woude, D.
Abstract : Background: Smoking is associated with the presence of autoantibodies in various diseases, such as chronic obstructive pulmonary disease (COPD) 1, systemic lupus erythematosus (SLE) 2 and polymyositis 3 . In rheumatoid arthritis (RA), smoking is assumed to be specifically associated with the presence of anti-citrullinated protein antibodies (ACPA), with smoking putatively leading to increased pulmonary citrullination. 4 Objectives: To investigate whether the association of smoking with RA is limited to ACPA-positive disease, or whether smoking is associated with autoantibody-positive RA in general. Methods: A meta-analysis based partly on published data (2 cohorts) 4, 5, and partly on new data (4 cohorts) was performed using 6 cohorts of RA patients from 5 countries: United Kingdom, Sweden, Norway, Japan, and the Netherlands. Complete data on rheumatoid factor (RF)-, ACPA-status and tobacco exposure were available for 7055 RA patients. The odds ratios (ORs) and 95% confidence intervals (95% CIs) associated with the presence of RF, ACPA or both were calculated by logistic regression comparing previous and current smokers with non-smokers, and using the ACPA-negative RF-negative RA patients as the reference category, since not all cohorts had matched controls. Results: There was no significant association between tobacco exposure and seropositive RA in patients who were positive for only one antibody, being either RF (n = 644, OR 1.04, 95% CI 0.75 – 1.44) or ACPA (n = 770, OR 1.00, 95% CI 0.83 – 1.22). However, smoking was significantly associated with double-positive (ACPA-positive and RF-positive) RA (n = 3598, OR 1.61, 95% CI 1.31 – 2.00). When double-positive patients were compared to single-positive patients, the effect of the additional presence of RF or ACPA was comparable; OR for RF: 1.42 (1.20 – 1.67), OR for ACPA: 1.49 (1.25 – 1.87). Conclusions: Smoking is not associated with ACPA-positive RA as such, but rather with the concurrent presence of multiple autoantibodies (RF and ACPA) in RA patients. In light of the association between smoking and autoantibodies in other diseases such as SLE and COPD, these data indicate that smoking predisposes to the development of auto-antibodies in general, and not to the development of ACPA per se. References: Feghali-Bostwick C. A. et al. 2008 Am J Respir Crit Care Med. 177(2):156-63 Freemer M. M. et al. 2006 Ann Rheum Dis. 65(5): 581-4 Chinoy H. et al. 2012 2012 Ann Rheum Dis. 71(6): 961-5 Klareskog L. et al. 2006 Arthritis Rheum. 54(1): 38-46. Morgan A. W. et al. 2009 Arthritis Rheum. 60(9): 2565-76 Disclosure of Interest: None Declared